The Mechanical Properties of a High Volume Natural Pozzolan Roller Compacted Concrete for Dams – Laboratory and Field Trials - Karuge, Amos; Mumenya, Siphila; Abuodha, Silvester; Munyua, Muthomi (LPPM Universitas Andalas, 2025)
This article reports the experimental findings of critical thermo-mechanical properties of RCC containing a high proportion of natural pozzolan as a supplementary cementitious material for Roller Compacted Concrete (RCC) dam construction, and was accomplished through laboratory and field trials. Natural pozzolan such as volcanic ash is a promising alternative to the industrial supplementary cementitious materials (SCM) such as flyash especially where the industrial SCM are economically unavailable as well as due to their expected shortage in the near future following greener energy sources and the need to reduce carbon emissions of concrete. Based on this research, the RCC with a cement replacement of up to 68% with natural pozzolan has produced satisfactory mechanical properties for dam construction and with nearly ideal thermal properties. The results are comparable to other international RCC dams and the RCC mix is considered appropriate for construction of a high quality and durable dam structure whilst contributing to sustainable construction.